PERANCANGAN SISTEM INFORMASI PERSEDIAAN GUDANG MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI PT. MITRADEKA MANDIRI BANDUNG - Yudhi Yanuar; Gilang Alwi Kusumah (POLITEKNIK PIKSI GANESHA, 2018)
This research resulted in information system application of stock warehouse. Which focuses on sales of motorcycle and auto spare parts. Where the data warehouse becomes very important to know whether the stock of goods is still there or has run out. Warehouse Stock Information System aims to facilitate the processing of data flow of goods, both incoming and outgoing goods. This created system is incorporated into the application software that is centrally stored using the MySQL database server. As for the interface design that connects the database with the user application using Microsoft Visual Studio 2010. So it can be concluded, that this application can minimize errors that often occur and develop the company to a better direction in the data processing in the warehouse.